Presentation is loading. Please wait.

Presentation is loading. Please wait.

Solving Systems Using Substitution

Similar presentations


Presentation on theme: "Solving Systems Using Substitution"— Presentation transcript:

1 Solving Systems Using Substitution

2 Substitution Sometimes you don’t have a graphing calculator to use.
Substitution allows you to solve a one-variable equation. One of the equations should be in either y = or x = form. Replace that variable in the other equation with the stuff on the right side.

3 Example 1 Solve y = 2x and 7x – y = 15
Replace the y in the second equation with what y is equal to in the first equation 7x – (2x) = 15 Simplify: 5x = 15 Solve: x = 3 Now, replace x in either equation with 3 to find y y = 2(3) y = 6 so the solution is (3, 6) Check in the second equation 7(3) – (6) = 15 21 – 6 = 15 is true so the solution is (3, 6)

4 Example 2 Solve: y = x + 5 and 4x + y = 20
Replace the y in the second equation with “x + 5” 4x + (x + 5) = 20 Simplify: 5x + 5 = 20 Solve: 5x = x = 3 Replace the x in the first equation with 3 y = 3 + 5 y = 8 (3, 8) Check your results.

5 Example 3 Solve: x = -2y – 1 and 4x – 4y = 20
Replace the x in the second equation with “-2y – 1” 4(-2y – 1) – 4y = 20 Distribute -8y – 4 – 4y = 20 Simplify -12y – 4 = 20 Solve -12y = y = -2 Replace the y in the first equation with 2 x = -2(-2) - 1 x = 3 (3, -2) Check your work.

6 Example 4 Solve: y = 2x + 3 and x – 2y = 3
Replace y with 2x + 3 in the second equation. x – 2(2x + 3) = 3 Distribute the –2 x – 4x – 6 = 3 Simplify x – 6 = 3 Solve x = x = -3 Replace x with –3 in the first equation y = 2(-3) y = -3 So, the solution is (-3, -3) (Check it in the 2nd equation too.)

7 Try these… x + y = 38 x = 2y – 25 y = x + 2.8 y + 4.6 = 2x y = x + 4
(17, 21) (7.4, 10.2) (1, 5) (20, 70)


Download ppt "Solving Systems Using Substitution"

Similar presentations


Ads by Google